Understanding and quantifying the immune microenvironment in hepatocellular carcinoma - Osorio, Juan C.; Harding, James J. (Translational Gastroenterology and Hepatology; Vol 3 (December 2018): Translational Gastroenterology and Hepatology, 2018)
Kim and colleagues reported recently on the molecular and functional phenotypes of tumor-infiltrating lymphocytes (TILs) derived from a cohort of patients with early stage hepatocellular carcinoma (HCC) (1). Briefly, cytometric methods were employed to isolate and to interrogate TILs and hepatic lymphocytes from 90 surgically-resected specimens from a single academic center.